Rurality and migration: sociocultural change in the communities of the sub-basin of the Jabonal river, Esparza, Puntarenas - Madrigal, Javier A. (2022)
The article aims to analyze the main socio-cultural changes in some small towns in the north of the canton the Esparza, province of Puntarenas. At present, they maintain a series of characteristics associated with rurality, in a context of urban growth in the Central Pacific Region, before this a view is provided from some of the inhabitants through an anthropological analysis and participant action research. The information collected indicates transformations in demography, landscape and productive activities. Within the contributions of the research, a description of the formation of these towns in the long term, since its foundation at the end of the 19th century, is developed. In addition, the importance of community organization in the construction of infrastructure is analyzed, as well as the characteristics of the economy. After analyzing this context, the discussion on the changes that have occurred in recent decades, linked to the concept of new rurality, is developed.